Benefits of Repetitive Transcranial Magnetic Stimulation (rTMS) for Spastic Subjects: Clinical, Functional, and Biomechanical Parameters for Lower Limb and Walking in Five Hemiparetic Patients. (29th April 2014) - Terreaux, Luc; Gross, Raphael; Leboeuf, Fabien; Desal, Hubert; Hamel, Olivier; Nguyen, Jean Paul; Pérot, Chantal; Buffenoir, Kévin
Abstract : Introduction. Spasticity is a disabling symptom resulting from reorganization of spinal reflexes no longer inhibited by supraspinal control. Several studies have demonstrated interest in repetitive transcranial magnetic stimulation in spastic patients. We conducted a prospective, randomized, double-blind crossover study on five spastic hemiparetic patients to determine whether this type of stimulation of the premotor cortex can provide a clinical benefit. Material and Methods. Two stimulation frequencies (1 Hz and 10 Hz) were tested versus placebo. Patients were assessed clinically, by quantitative analysis of walking and measurement of neuromechanical parameters ( H and T reflexes, musculoarticular stiffness of the ankle). Results. No change was observed after placebo and 10 Hz protocols. Clinical parameters were not significantly modified after 1 Hz stimulation, apart from a tendency towards improved recruitment of antagonist muscles on the Fügl-Meyer scale. Only cadence and recurvatum were significantly modified on quantitative analysis of walking. Neuromechanical parameters were modified with significant decreases in H max ⁡ /M max ⁡ and T /M max ⁡ ratios and stiffness indices 9 days or 31 days after initiation of TMS. Conclusion. This preliminary study supports the efficacy of low-frequency TMS to reduce reflex excitability and stiffness of ankle plantar flexors, while clinical signs of spasticity were not significantly modified.